ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DI DESA LERO KECAMATAN SINDUE KABUPATEN DONGGALA - Mulviana M. Amin; Alimudin Laapo (Universitas Negeri Gorontalo, 2021)
The objectives of this research are: (1) to find out the Welfare Level of the Fishermen according to the World Bank (2) to find out the Welfare Level of the Lero Village Fishermen based on the Central Bureau of Statistics. Data were collected using observation, questionnaires, interviews, and documentation. Data analysis used in measuring fishermen's welfare using the income approach and BPS criteria. The results of the research show that (1) Based on the net income of fishermen for a month is IDR. 839.413, which means less than World Bank standards, it can be categorized as poor or not yet prosperous. (2) Based on the sum of the calculation of the recapitulation of welfare indicators based on the Central Bureau of Statistics criteria, it shows that the fishermen are at a moderate level of welfare, with a total score of 15.